Finding Ways to Get More Students in the Stands - Fiez, Michael; Karnopp, Kelsey; Miller, Katie Dean; Pelissero, Taylor; Rudd, Cassandra; Tyink, Stephanie; Zeiter, Nathan (My University, 2015)
The University of Wisconsin-Eau Claire Blugold athletics program has been seeing a negative decline in student attendance at athletics events during the past five seasons. Students who are uninterested in school spirit-related activities, like sports, become disinterested alumni who are less likely to be future donors. This is why it is important to find ways to increase student attendance at athletic events. The first step in finding ways to increase student attendance is performing formative research on the target audience to determine their motivations for attending and the best ways to distribute promotional materials to them.
Color poster with text, graphs, and images.
Keywords: Sports attendance; Blugold athletics; Sports fans; Posters